Reading and Viewing Ability of Third Grade Students in Elementary School - Sumarmi, Shela Apriningtyas; Nur Amalia (Universitas Pendidikan Ganesha, 2023)
The observations showed that the ability to read and watch students was low. Therefore, this study aims to analyze the implementation of Indonesian language learning and the reading and viewing abilities of third-grade elementary school students. This research was conducted in grade 3 with 20 students and the homeroom teacher. This type of research is descriptive qualitative. The techniques used in collecting data are observation, documentation, and interviews. The data analysis technique used is data reduction, data presentation, and conclusion. First is the ability to grasp the meaning of reading; 11 people cannot grasp the meaning of reading. The second indicator, the ability to grasp meaning in reading, needs repetition in explaining questions so students can catch meaning in reading. The ability to see students has three indicators, namely first, watching when playing a fairy tale video, students look calm and focused. Second, listening. In this skill, students listen to videos well, which can be seen from the response when asked questions by the teacher regarding the video. Third, looking closely, it was found that 16 students could not answer the given LKPD questions. It was concluded that the implementation of learning Indonesian on the ability to read and watch using strategies, methods and media had yet to achieve the indicators in the learning objectives.